A Survey on the Occurrence of Livestock Diseases and Constrains in Controlling those Diseases in Maharashtra - Das, S. K.; Aithal, H. P.; Bhilegaonkar , K. N. (International Journal of Livestock Research, 2020)
Feedback of 344 veterinary officers of Maharashtra state was taken regarding the occurrence of infectious disease, systemic disease, reproductive disorders and constrains faced by them in controlling those diseases in different regions of Maharashtra in pre constructed format. It was revealed that PPR (2.30 ± 0.08), Mastitis (1.81 ± 0.06) and repeat breeding (1.73 ± 0.05) were most important infectious disease, systemic disease and reproductive disease respectively. Most important difficulty in controlling infectious diseases, difficulty in treatment of diseases and most important causes for reproductive problems at field level were found to be “Non cooperation from animal owners (2.16 ± 0.07)”, “high cost of treatment (2.53 ± 0.07)” and “nutritional deficiencies (1.66 ± 0.06)” respectively. Region wise analysis of data revealed that PPR was the most prevalent infectious disease in all the six regions of Maharashtra except in Pune. Mastitis was the most prevalent systemic disease in five regions i.e. Mumbai, Pune, Aurangabad, Latur and Amaravati. Repeat breeding was the predominant reproductive problem in all the seven regions of the state. Nutritional deficiency was found to be the main cause of reproductive problems.